1994
DOI: 10.1007/bf02840763
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependence of time-dependent friction and electric field fluctuations

Abstract: Molecular-dynamics simulations of a model dipolar system containing two ions have been carried out to study the effect of temperature on the time-dependent friction (((t)) on the solute ions as well as the electric fields in the vicinity of the ions. It is found that with an increase in temperature, (/) the magnitude of ((0) increases and (ii) the electric field time correlation functions decay more rapidly at higher temperatures due to faster reorientations and translational diffusion of the molecules. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…They found that the cross-terms are not zero. Later studies carried out by Sridhar et al using a different water potential came to similar conclusions. Recently, Chong and Hirata have considered a further extension of the theory of ion mobility in a dipolar solvent in which the cross-terms are not neglected.…”
Section: The Friction On An Ionmentioning
confidence: 53%
“…They found that the cross-terms are not zero. Later studies carried out by Sridhar et al using a different water potential came to similar conclusions. Recently, Chong and Hirata have considered a further extension of the theory of ion mobility in a dipolar solvent in which the cross-terms are not neglected.…”
Section: The Friction On An Ionmentioning
confidence: 53%
“…Later Tembe and coworkers [32,33] and Koneshan et al [34] also confirmed that cross terms cannot be neglected.…”
Section: Introductionmentioning
confidence: 92%
“…Wolynes in his attempt to formulate a microscopic theory of dielectric friction identified the term ζ HH as the Stokes friction and ζ SS as the dielectric friction and neglected the other two terms. 7,27 Later by theoretical approach 6 and by computer simulations, 8,16,17,[31][32][33][34] several studies confirmed that the cross terms cannot be fully neglected.…”
Section: Microscopic Theories For Monatomic Ionsmentioning
confidence: 97%